2017
DOI: 10.1109/tcyb.2016.2555307
|View full text |Cite
|
Sign up to set email alerts
|

Finite Time Fault Tolerant Control for Robot Manipulators Using Time Delay Estimation and Continuous Nonsingular Fast Terminal Sliding Mode Control

Abstract: In this paper, a novel finite time fault tolerant control (FTC) is proposed for uncertain robot manipulators with actuator faults. First, a finite time passive FTC (PFTC) based on a robust nonsingular fast terminal sliding mode control (NFTSMC) is investigated. Be analyzed for addressing the disadvantages of the PFTC, an AFTC are then investigated by combining NFTSMC with a simple fault diagnosis scheme. In this scheme, an online fault estimation algorithm based on time delay estimation (TDE) is proposed to ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
253
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 386 publications
(253 citation statements)
references
References 67 publications
0
253
0
Order By: Relevance
“…The stability of higher-order super-twisting sliding mode controller for any match uncertainties has been proved by Kamal and Bandyopadhyay in [45]. The authors in [32,40,41] have demonstrated the robustness of super-twisting higher-order sliding mode observer to uncertainties. Therefore, the proposed method can be used for the control of an uncertain robot manipulator without stability problems.…”
Section: Proposed Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…The stability of higher-order super-twisting sliding mode controller for any match uncertainties has been proved by Kamal and Bandyopadhyay in [45]. The authors in [32,40,41] have demonstrated the robustness of super-twisting higher-order sliding mode observer to uncertainties. Therefore, the proposed method can be used for the control of an uncertain robot manipulator without stability problems.…”
Section: Proposed Methodsmentioning
confidence: 94%
“…Based on [31,32,41] the super-twisting higher order sliding mode observer has a finite time convergence. Thus, the stability of higher-order super-twisting sliding mode controller and super-twisting higher-order sliding mode observer has been guaranteed separately.…”
Section: Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To acquire benefits of TSM and FO control, and avoid the singularity problem, sliding surface has been designed in [15,19]. Motivated by the aforementioned techniques, accurate and rapid control performance for an n-degree of freedom (n-DOF) manipulators in finite-time, the following referred FONFTSM surface can be selected as…”
Section: Sliding Surface Designmentioning
confidence: 99%
“…For robotic applications, there are few FTC methods that have been proposed, concern with the finite-time convergence. In [19], Non-Singular Fast Terminal Sliding Mode Control (NFTSMC) has been used to obtain rapid convergence and improvement in chattering and singularity problem, while time delay estimation (TDE) based FTC has been utilized for estimation of uncertainties and actuator faults. Since, the TDE is developed by inserting the delay in control method, which may deteriorate the performance of the system.…”
Section: Introductionmentioning
confidence: 99%